A review of graphical user interfaces of OpenSees software framework - Shabani, Amirhosein (Frontiers in Built Environment, 2023)
Seismic vulnerability assessment is crucial for evaluating the resilience of structures. OpenSees, an open-access and versatile tool, plays a pivotal role in accurately simulating the complex behavior of structures subjected to seismic loads. However, lacking a built-in graphical user interface (GUI) is one of the limitations of OpenSees that can hinder usability and accessibility. Moreover, users must rely on command-line inputs and scripts for interaction, potentially limiting its adoption by nonprogrammers. To address this, several GUIs were designed as pre-and post-processor for OpenSees. In this study, 15 GUIs were categorized as open access or commercial. The functionalities and features of the GUIs, such as open-source nature, three-dimensional (3D) modeling and visualization capabilities, automation of incremental dynamic analysis (IDA), and simplification of soil-structure interaction (SSI) modeling, were examined. Note that certain GUIs were introduced with a focus on modeling and analysis of specific structures that were reviewed in this study. This mini-review aims to guide OpenSees users in choosing an appropriate GUI for their projects and support developers in improving existing GUI functionality or creating advanced GUIs that comprehensively cater to users' needs.